1994
DOI: 10.1002/pros.2990250107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of naftopidil on urethral obstruction in benign prostatic hyperplasia: Assessment by urodynamic studies

Abstract: Thirty-two patients with voiding dysfunction attributable to symptomatic benign prostatic hyperplasia were treated with naftopidil, an alpha 1-blocker, at doses of 25-75 mg/day for 4-6 weeks. The efficacy of the drug was assessed from the changes in urinary symptoms and urodynamic data. Total symptom scores were significantly reduced after treatment (P < 0.001). Average flow rate and maximum flow rate were significantly increased (P < 0.001 and P < 0.001, respectively), and residual urine volume, residual urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…Detrusor overactivity, however, has also been reported to occur in other lesions such as benign prostatic hypertrophy [6, 7]. Detrusor areflexia is a typical urodynamic finding in lower lumbar spine lesions [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detrusor overactivity, however, has also been reported to occur in other lesions such as benign prostatic hypertrophy [6, 7]. Detrusor areflexia is a typical urodynamic finding in lower lumbar spine lesions [1].…”
Section: Discussionmentioning
confidence: 99%
“…Such postoperative improvements in detrusor overactivity strongly suggest that the lower lumbar spine lesions caused detrusor overactivity. If detrusor overactivity does not improve after surgery, there may be other causative factors, such as bladder outlet obstruction [6, 7], other neurological disorders and aging. Patients with bladder outlet obstruction and disorders due to other upper motor neurons lesions were excluded from the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-1 adrenergic receptor antagonists (alpha-1 antagonists) decrease the prostatic urethral closing pressure. [2][3][4][5][6] These antagonists have been used for the treatment of BPH, and can not only improve voiding disorders but also assist in the treatment of collecting disorders. 2,5,7 Among non-selective alpha-1 antagonists used for the treatment of BPH, terazosin hydrochloride (terazosin), prazosin hydrochloride, and urapidil have also been employed for the treatment of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] These antagonists have been used for the treatment of BPH, and can not only improve voiding disorders but also assist in the treatment of collecting disorders. 2,5,7 Among non-selective alpha-1 antagonists used for the treatment of BPH, terazosin hydrochloride (terazosin), prazosin hydrochloride, and urapidil have also been employed for the treatment of hypertension. [8][9][10] Our previous study showed that elderly patients with nocturia had a higher blood pressure and higher serum catecholamine levels when compared with healthy elderly controls.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently alpha 1-adrenoceptor antagonists have become the first-line treatment for the relief of BPH symptoms (11). Naftopidil, the alpha 1A/D-adrenoceptor antagonist, has been widely used to BPH because it reduces resistance in the prostatic urethra (31). Multiple studies using rats have shown that naftopidil inhibits the micturition reflex after oral administration (9,22), intravenous injection (2), injection into the medial frontal lobe (14), and after injection into the subarachnoid space at the lumbosacral cord level (26).…”
mentioning
confidence: 99%